Evolution of supraglacial lakes on Sermeq Avannarleq glacier, Greenland using Google Earth Engine - Dongyu Zhu; Chunxia Zhou; Yikai Zhu; Boyang Peng (Journal of Hydrology: Regional Studies, 2022)
Study region: This study investigates the Supraglacial lakes (SGLs) of Sermeq Avannarleq glacier. This glacier is in southwest Greenland, which has active glacial meltwater. Study focus: Supraglacial lakes (SGLs) are an essential part of the hydrological systems of ice sheets, and their development is vital for determining the stability of ice sheets. This paper use 188 scenes of Landsat images during the melting season from 2000 to 2020 with Google Earth Engine to analyze the seasonal changes of the SGLs. New hydrological insights: 1) The area, volume, and depth of the SGLs, increased, indicating the increasing melt in this area from 2000 to 2020. 2) the SGLs development peaked at 190–200 days of the year. The melting area significantly expanded at the initial stage, while the melting depth change was more significant than the area at the later stage. 3) The elevation reached by the SGLs advanced approximately 300 m inland from 1400 m to 1700 m elevation. The convergence of small lakes (<0.25 km2), the reappearance of buried lakes, and the distribution of SGLs zone shift inland occurred during the SGLs development. 4) High recurrence lake area was mostly below 2 km2, and the recurrence rate of water were related to geographical factors. This study can provide technical support and a point of reference for monitoring the surface hydrological systems in Greenland ice sheet.